Fumarate hydratase as a therapeutic target in renal cancer. (1st September 2020) - Kancherla, Priyanka; Daneshvar, Michael; Sager, Rebecca A.; Mollapour, Mehdi; Bratslavsky, Gennady
ABSTRACT: Introduction: Renal cell carcinoma (RCC) is a heterogeneous group of cancers that can occur sporadically or as a manifestation of various inherited syndromes. Hereditary leiomyomatosis and renal cell carcinoma (HLRCC) is one such inherited syndrome that predisposes patients to HLRCC-associated RCC. These tumors are notoriously aggressive and often exhibit early metastases. HLRCC results from germline mutations in the FH gene, which encodes the citric acid cycle enzyme fumarate hydratase (FH). FH loss leads to alterations in oxidative carbon metabolism, necessitating a switch to aerobic glycolysis, as well as a pseudohypoxic response and consequent upregulation of various pro-survival pathways. Mutations in FH also alter tumor cell migratory potential, response to oxidative stress, and response to DNA damage. Areas covered: We review the mechanisms by which FH loss leads to HLRCC-associated RCC and how these mechanisms are being rationally targeted. Expert opinion: FH loss results in the activation of numerous salvage pathways for tumor cell survival in HLRCC-associated RCC. Tumor heterogeneity requires individualized characterization via next-generation sequencing, ultimately resulting in HLRCC-specific treatment regimens. As HLRCC-associated RCC represents a classic Warburg tumor, targeting aerobic glycolysis is particularly promising as a future therapeutic avenue.